Enhancing organizational processes for service innovation: strategic organizational counseling and organizational network analysis - Marocco, Silvia; Marini, Mara; Talamo, Alessandra (Frontiers in Research Metrics and Analytics, 2024)
Previous studies have primarily focused on product innovation, overlooking the examination of organizational processes. This limited perspective poses a theoretical and practical gap as it primarily considers the external aspects of innovation. On the contrary, organizational processes play a crucial role in improving and creating internal operations necessary for product/service innovation success. To this aim, this paper presents a novel approach to enhancing service innovation within complex organizations by integrating Strategic Organizational Counseling (SOC) and Organizational Network Analysis (ONA) methodologies. More specifically, SOC supports organizations in understanding and defining the professional families that need to be triggered in the service ideation, delivery and commercialization process, especially in the case of complex organizations with multiple departments. Secondly, ONA enables the identification of the intra-organizational nodes within the professional families that, due to their social position and other personal characteristics, can be actively engaged as Ambassadors for the promotion of innovation practices. By focusing on intra-organizational processes, understanding role-related needs, and selecting influential organizational actors, this approach provides a new perspective on the service innovation process, assuming both a micro and macro viewpoint. The paper also highlights the importance of cyclically monitoring the proposed workflow to adapt to the dynamic nature of innovation.